Prosopis invasions in South Africa: Population structures and impacts on native tree population stability. (March 2015) - Shackleton, Ross T.; Le Maitre, David C.; Richardson, David M.
Abstract: Several Prosopis taxa are widespread invaders that have negative impacts on biodiversity and human livelihoods globally. Better knowledge of the impacts and ecology of invasive Prosopis species is required to support and inform management interventions. Prosopis was introduced to South Africa and has become the second most widespread invasive alien plant taxon in the country. We compare population structures of invasive Prosopis populations in different part of South Africa, and quantify the effects of Prosopis invasions on native tree populations using size-class distribution (SCD) curves. Kolmogorov–Smirnov tests, regressions, quotients, and Permutation Indices were used to compare size-class distributions and assess population stability. Prosopis population structures differed across South Africa. Those along perennial rivers and areas in the Succulent Karoo biome had fewer juvenile plants. Prosopis in South Africa also has higher recruitment (% juvenile plants) than in other areas like Australia. Prosopis invasions are having a negative effect on the stability of native tree populations in South Africa, and are linked to increased mortality of native trees. Improved management of Prosopis is needed. Highlights: Prosopis invasion ecology in South Africa differs across spatial scales. Prosopis is recruiting rapidly and shows good population structure curves in South Africa. Prosopis invasions are having a negative influence of the population stability of native trees. Prosopis invasions are increasing the mortality of native trees. Increased management of Prosopis is greatly needed in South Africa.